Land use/land cover changes and its impact on runoff using SWAT model in the upper Prek Thnot watershed in Cambodia - Khorn, Norin; Ismail, Mohd Hasmadi; Siti Nurhidayu; Kamarudin, Norizah; Sulaiman, Mohd Sofiyan (Springer, 2022)
Land use/land cover changes (LULC) may result in water shortages, flood risk and soil erosion, contributing to the degradation of living situations. Therefore, studying the impacts of LULC changes on water resources is critical to watershed management. This study aims to determine LULC change and its impact on runoff and other hydrological components, including groundwater, water yield, percolation and evapotranspiration in the Upper Prek Thnot watershed from 2006 to 2018, by using SWAT modelling. Results showed that LULC of the Upper Prek Thnot watershed experienced such significant changes during these 13 years. The main modification in the study area was converting forest area into agricultural land, which accounts for 39%. This was followed by increased rubber plantation, built-up area, barren land and water bodies, and decreased wood shrubs. The changes in land use caused an increase in annual average surface runoff (36%), water yield (2%), and a decrease in groundwater (24%), percolation (8%) and evapotranspiration (1%). If the forest area is converted to agricultural land, mainly when the conversion occurs in large numbers, the hydrological elements will be significantly affected. Consequently, due to a noticeable alteration of LULC in the study area, a sound strategic management plan should be applied considerably to ensure ecosystem services sustainability in the watershed area.